Cover Feature: Molecular Functionalization of NiO Nanocatalyst for Enhanced Water Oxidation by Electronic Structure Engineering (ChemSusChem 22/2020). Issue 22 (27th October 2020) - Fan, Lizhou; Zhang, Biaobiao; Qiu, Zhen; Dharanipragada, N. V. R. Aditya; Timmer, Brian J. J.; Zhang, Fuguo; Sheng, Xia; Liu, Tianqi; Meng, Qijun; Inge, A. Ken; Edvinsson, Tomas; Sun, Licheng
Abstract : The Cover Feature shows an efficient NiO‐C6 F5 water oxidation catalyst, which was constructed by molecular functionalization at the nanoparticle surface. By rational electronic modulation, a comprehensive understanding on structure–activity was discovered. More information can be found in the Full Paper by L. Fan et al .